Interventions addressing risk factors of ischaemic heart disease in sub-Saharan Africa: a systematic review. Issue 7 (5th July 2016) - Ebireri, Jennifer; Aderemi, Adewale V; Omoregbe, Nicholas; Adeloye, Davies
Abstract : Background: Ischaemic heart disease (IHD) is currently ranked eighth among the leading causes of deaths in sub-Saharan Africa (sSA). Yet, effective population-wide preventive measures targeting risks in the region are still largely unavailable. We aimed to review population-wide and individual-level interventions addressing risk factors of IHD among adults in sSA. Methods: A systematic search of MEDLINE, EMBASE, Global Health and AJOL was conducted to identify studies focusing on population-wide and individual-level interventions targeting risks of IHD among adults in sSA. We conducted a detailed synthesis of basic findings of selected studies. Results: A total of 2311 studies were identified, with only 9 studies meeting our selection criteria. 3 broad interventions were identified: dietary modifications, physical activity and community-based health promotion measures on tobacco and alcohol cessation. 3 studies reported significant reduction in blood pressure (BP), and another study reported statistically significant reduction in mean total cholesterol. Other outcome measures observed ranged from mild to no reduction in BP, blood glucose, body mass index and total cholesterol, respectively. Conclusions: We cannot specify with all certainty contextually feasible interventions that can be effective in modifying IHD risk factors in population groups across sSA. We recommend more research on IHD, particularly on the understanding of the burden, geared towards developing and/or strengthening preventive and treatment interventions for the disease in sSA.